Design Analysis of the Welding Fume Blower Bracket in the Welding Laboratory at Politeknik Sinar Mas Berau Coal - Pradana, Ilmawan Suryapradana; Safitriani, Dewi; Adi Nugraha, Kris; Fadilman Sinambela, Haksa; Musliadi (DINAMIS, 2024)
Sinar Mas Berau Coal Polytechnic has equipped a welding laboratory with blower installation according to welding standards. Installing the blower requires a bracket as a holder. For the design, the type of material used is ASTM A36 material and analyzes the simulation of fume blow welding brackets with angle iron measuring 5x5 cm. In implementing the working steps for a sturdy and strong bracket within the tolerance limits explained as follows, namely planning and modeling the frame, simulating and calculating theoretically. Based on the design and testing of the welding fume blower bracket using the Autodesk Inventor 2018 application with a given load of 186,778 N. This test tests the maximum and minimum von Mises stress, displacement, safety factor, which is calculated using the Autodesk Inventor 2018 simulation. The results compare the theory and simulation. ASTM A36 material has a yield stress value of 248.225 Mpa, obtained by von Misese stress simulation calculations of 51.64 Mpa and theoretical calculations of 45.88 Mpa. The results of the von Mises stress deviation between simulation and theory are 11.29%. For displacement, theoretical calculations get a figure of 0.02247 and simulation results get a value of 0.09468. The results of the displacement deviation between simulation and theory are 3.21%. For the safety factor obtained in the analysis using software and theoretical calculations, the welding fume blower bracket obtained a safety factor value of 4.80 with theoretical calculations and 5.41. The results of the safety factor deviation between simulation and theory are 12.56%.